Tingkat Kepuasan Masyarakat Terhadap Pelayanan Publik (Evaluasi Implementasi Program Beras Sejahtera Di Kota Palopo) - Muhammad Ardiansyah Makmur; Andi Agustang; Andi Muhammad Idkhan (Jurnal Sosio Sains, 2021)
The Prosperous Rice support program in Palopo City which has been going since 2017 based on the results of field observations and investigations from various information media portals, there are many weaknesses in service delivery, starting from the aspect of collecting data on recipients, inappropriate distribution time to the quality of rice which many people complain about. So it is necessary to evaluate public services by measuring the level of community satisfaction with prosperous rice services in Palopo City. The method used in this study is a survey method with a quantitative approach with the total population in this study being all recipients of the Prosperous Rice (Rastra) 3,928 families in the 2021 fiscal year in Palopo City, with regional and accidental sampling techniques with a total of 186 people. Data collection techniques with questionnaires, observations and documentation review and data analysis of Likert scale classification with interpretation criteria very satisfied, satisfied, quite satisfied, and dissatisfied. The results showed that the level of satisfaction was 81.45 or in the very satisfied category. This is by open statements and field observations that the community has received services that are under the 14 indicators of the community satisfaction survey.